Cost analysis of the WHO-HEARTS program for hypertension control and CVD prevention in primary health facilities in Ethiopia - Senait Alemayehu Beshah; Muhammad Jami Husain; Girma A. Dessie; Addisu Worku; Mussie Gebremichael Negeri; Bolanle Banigbe; Andrew E. Moran; Soumava Basu; Deliana Kostova (Public Health in Practice, 2023)
Background: In 2020, Ethiopia launched the Ethiopia Hypertension Control Initiative (EHCI) program to improve hypertension care using the approach described in the WHO HEARTS technical package. Objective: To estimate the costs of implementing the HEARTS program for hypertension control and cardiovascular disease (CVD) prevention in the primary care setting in Ethiopia for adult primary care users in the catchment area of five examined facilities. Study design: This study entails a program cost analysis using cross-sectional primary and secondary data. Methods: Micro-costing facility surveys were used to assess activity costs related to training, counselling, screening, lab diagnosis, medications, monitoring, and start-up costs at five selected health facilities. Cost data were obtained from primary and secondary sources, and expert opinion. Annual costs from the health system perspective were estimated using the Excel-based HEARTS costing tool under two intervention scenarios – hypertension-only control and a CVD risk management program, which addresses diabetes and hypercholesterolemia in addition to hypertension. Results: The estimated cost per adult primary care user was USD 5.3 for hypertension control and USD 19.3 for integrated CVD risk management. The estimated medication cost per person treated for hypertension was USD 9.0, whereas treating diabetes and high cholesterol would cost USD 15.4 and USD 15.3 per person treated, respectively. Medications were the major cost driver, accounting for 37% of the total cost in the hypertension control program. In the CVD risk management scenario, the proportions of medication and lab diagnostics of total costs were 18% and 64%, respectively. Conclusions: The results from this study can inform planning and budgeting for HEARTS scale-up to prevent CVD across Ethiopia.